2020
DOI: 10.3390/app10051644
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Gratifications on Augmented Reality Games: An Examination of Pokémon Go

Abstract: Users are attracted by augmented reality games to fulfil their needs. Two objectives are proposed: (1) to research the motivations of those using augmented reality mobile games; (2) to define a structural model based on Uses and Gratifications Theory for the adoption of augmented reality mobile games. The present study examines the case of Pokémon Go. The model is composed of eight constructs: enjoyment, fantasy, escapism, social interaction, social presence, achievement, self-presentation and continuance inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 90 publications
0
41
0
Order By: Relevance
“…Thus, for example, researchers [ 11 ] analyzed the gamers´ attitude and intention to play online games with a model that incorporated variables such as, visual appeal, escape from reality and self-efficiency. Moreover, a study [ 22 ], using a seven-factor model (enjoyment, fantasy, escapism, social interaction, social presence, achievement, and self-presentation), determined the influences on continuance intention to play online games. However, despite the existence of these studies, positive effects of the online games use have been poorly studied.…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Thus, for example, researchers [ 11 ] analyzed the gamers´ attitude and intention to play online games with a model that incorporated variables such as, visual appeal, escape from reality and self-efficiency. Moreover, a study [ 22 ], using a seven-factor model (enjoyment, fantasy, escapism, social interaction, social presence, achievement, and self-presentation), determined the influences on continuance intention to play online games. However, despite the existence of these studies, positive effects of the online games use have been poorly studied.…”
Section: Research Framework and Hypothesis Developmentmentioning
confidence: 99%
“…The U&G theoretical approach is becoming more prominent with the rise of new interactive media in which users enjoy a greater degree of participation [ 29 ]. Models developed from U&G theory have evolved and are being widely used and tested in a range of contexts, for example, to explore the use of social networks and their effects [ 28 , 30 ], the use of video games [ 31 ], virtual social worlds [ 32 ], smart speakers [ 33 ] or innovations in the way of watching television [ 34 , 35 ]. Live streaming platforms have come to represent a novel hybrid of conventional television, YouTube and a social network; the content they provide is primarily—though not exclusively—video games.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies of intrinsic social and individual factors that affect motivation to play online games [12], [13] have reported that predictors of intention to play online games include achievement, enjoyment, and social affiliation. Moreover, the choice of a particular M-SNG depends on whether it fulfils their motivations, which in turn drive their usage [1], [32]. Thus, we propose that an evaluation of M-SNG player motivation should include achievement, enjoyment and social interaction.…”
Section: M-sng Player Motivationmentioning
confidence: 99%